CLUSTER MODEL FOR EXTENSIVE GIANT TIGER SHRIMP (Penaeus monodon Fab.) TO PREVENT TRANSMISSION OF WHITE SPOT SYNDROME VIRUS - Arief Taslihan; Richard Callinan; Jenny-Ann Torribio; Bambang Sumiarto; Kamiso Handoyo Nitimulyo (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2015)
White spot syndrome virus (WSSV) has become epidemic in Indonesia and affecting shrimp aquaculture interm of its production. White spot syndrome virus is transmitted from one to other ponds, through crustacean, included planktonic copepode as carrier for WSSV and through water from affected shrimp pond. A cluster model, consist of shrimp grow out ponds surrounded by non-shrimp pond as a role of biosecurity has been developed. The model aimed to prevent white spot virus transmission in extensive giant tiger shrimp pond. The study was conducted in two sites at Demak District, Central Java Province. As the treatment, a cluster consist of three shrimp ponds in site I, and two shrimp ponds in site II, each was surrounded by buffer ponds rearing only finfish. As the control, five extensive shrimp grow out ponds in site I and three shrimp grow out ponds in site II, with shrimp pond has neither applied biosecurity nor surrounded by non-shrimp pond as biosecurity as well considered as control ponds. The results found that treatment of cluster shrimp ponds surrounded by non-shrimp ponds could hold shrimp at duration of culture in the grow out pond (DOC) 105.6±4.5 days significantly much longer than that of control that harvested at 60.9±16.0 days due to WSSV outbreak. Survival rate in trial ponds was 77.6±3.6%, significantly higher than that of control at 22.6±15.8%. Shrimp production in treatment ponds has total production of 425.1±146.6 kg/ha significantly higher than that of control that could only produced 54.5±47.6 kg/ha. Implementation of Better Management Practices (BMP) by arranging shrimp ponds in cluster and surrounding by non-shrimp ponds proven effectively prevent WSSV transmission from traditional shrimp ponds in surrounding area.